Randomized controlled trial comparing quadratus Lumborum Block and Surgical Site Infiltration in Total Abdominal Hysterectomy: Efficacy Analysis - Sangeeta Dhanger; R L Jayavani; Bhavani Vaidiyanathan; Idhuyya Joseph Rajesh (Indian Journal of Pain)
Background: Total abdominal hysterectomy is a common surgical procedure associated with significant postoperative pain. Effective pain management techniques are critical for enhancing patient recovery and satisfaction. This study aimed to compare the efficacy of the quadratus lumborum block (QLB) with surgical site infiltration (SSI) in managing postoperative pain following total abdominal hysterectomy. Methods: In a randomized controlled trial, 60 female patients scheduled for total abdominal hysterectomy under spinal anesthesia were divided into two groups: QLB and SSI, with 30 patients in each group. However, due to incomplete data, 2 patients from the QLB group were excluded, resulting in 58 participants in the final analysis. The primary outcomes measured were the time to first request for analgesia and total morphine consumption within the first 24 h postoperatively. The secondary outcomes included patient satisfaction and the incidence of sleep disturbance due to pain. Results: Both the groups were comparable in terms of age, body mass index, American Society of Anesthesiologists grade, and duration of surgery. There was no significant difference in the time to first request for analgesia between the two groups. Although the mean total morphine consumption was higher in the SSI group, this difference was not statistically significant (P = 0.052035). In the first 2 h postoperation, the QLB group reported higher Verbal Analog Scale (VAS) scores, indicating more pain, but this difference leveled off in the subsequent 22 h. The time taken to administer the block was significantly longer in the QLB group compared to the SSI group. Conclusion: Both QLB and SSI are effective techniques for managing postoperative pain following total abdominal hysterectomy. Despite the longer time required to administer QLB and initially higher VAS scores, there were no significant differences in time to first analgesia request, total morphine consumption, or patient satisfaction between the two methods. The choice of pain management technique can therefore be based on the clinical setting, practitioner’s expertise, and patient preferences.